Long-Term Effects of Whole-Body Vibration on Human Gait: A Systematic Review and Meta-Analysis - Fischer, Matthieu; Vialleron, Thomas; Laffaye, Guillaume; Fourcade, Paul; Hussein, Tarek; Chèze, Laurence; Deleu, Paul-André; Honeine, Jean-Louis; Yiou, Eric; Delafontaine, Arnaud (Frontiers in Neurology, 2019)
Background: Whole-body vibration is commonly used in physical medicine and neuro-rehabilitation as a clinical prevention and rehabilitation tool. The goal of this systematic review is to assess the long-term effects of whole-body vibration training on gait in different populations of patients. Methods: We conducted a literature search in PubMed, Science Direct, Springer, Sage and in study references for articles published prior to 7 December 2018. We used the keywords “vibration”, “gait” and “walk” in combination with their Medical Subject Headings (MeSH) terms. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology was used. Only randomized controlled trials (RCT) published in English peer-reviewed journals were included. All patient categories were selected. The duration of Whole-Body Vibration (WBV) training had to be at least four weeks. The outcomes accepted could be clinical or biomechanical analysis. The selection procedure was conducted by two rehabilitation experts and disagreements were resolved by a third expert. Descriptive data regarding subjects, interventions, types of vibration, training parameters and main results on gait variables were collected and summarized in a descriptive table. The quality of selected studies was assessed using the PEDro scale. The level of evidence was determined based on the results of meta-analysis (effect size), statistical heterogeneity (I2). Results: Twenty-five studies were included in meta-analysis for quantitative synthesis. In elderly subjects, small but significant improvements in the TUG test were found in the WBV groups with a strong level of evidence. In stroke patients, significant improvement in the 6MWT was found after WBV interventions, with a strong level of evidence. Results were inconsistent in COPD patients. Similarly, the heterogeneous results in the TUG test in patients with knee osteoarthrosis make it impossible to draw a conclusion. Conclusions: WBV training can be effective for improving balance and gait speed in the elderly. The intervention is also effective in improving walking performance following stroke and in patients with knee osteoarthrosis. However, no effect was found on gait quality in the elderly or on balance in stroke and multiple sclerosis patients. The results are too heterogenous in COPD to conclude on the effect of the treatment.